1996
DOI: 10.1021/om950954b
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Promoted Oxidative π-Conjugation and Coupling of Substituted-Fulvalene-Type Ligands:  Synthesis and Crystal Structures of π-Conjugated C24H12(SiMe3)2 and the Dimer [C24H13(SiMe3)2]2

Abstract: The oxidation of the substituted-fulvalene dianion with group 13 metal halides yields dark green crystals of the stable π-conjugated fulvalene C24H12(SiMe3)2. Reaction of the fulvalene monoanion with the metal halides results in the oxidative coupling of the ligand to give the dimer [C24H13(SiMe3)2]2. These compounds, obtained rather unexpectedly during efforts to synthesize metal complexes of the fulvalene-type ligand, have been characterized by X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The compound crystallizes from dichloromethane in space group P 2 1 / n ; the monoclinic cell unit contains four molecules of (Tbf) 2 along with 4 equiv of dichloromethane (Figure ). An extraordinarily long C−C single bond between C1−C30 (1.615(2) Å) is found, nearly identical to the corresponding C−C bond in a comparable compound described by Malaba and Youngs . A nearly perfect face-to-face π−π stacking of the C5/C24 and C31/C41 rings is observed (distance of the ring centers 3.422 Å) …”
Section: Resultssupporting
confidence: 71%
“…The compound crystallizes from dichloromethane in space group P 2 1 / n ; the monoclinic cell unit contains four molecules of (Tbf) 2 along with 4 equiv of dichloromethane (Figure ). An extraordinarily long C−C single bond between C1−C30 (1.615(2) Å) is found, nearly identical to the corresponding C−C bond in a comparable compound described by Malaba and Youngs . A nearly perfect face-to-face π−π stacking of the C5/C24 and C31/C41 rings is observed (distance of the ring centers 3.422 Å) …”
Section: Resultssupporting
confidence: 71%
“…Warrener and co-workers report that, in addition to the well-known cycloaddition chemistry exhibited by molecules which contain the o -xylylene moiety, the dimerization of isoindenes via ene-type mechanisms can occur if a hydrogen atom is present at the C(2) position. It is also noteworthy that dimeric compounds closely related to 9 have received recent attention in the literature. Olmstead and co-workers have discussed the unexpected isolation of 10 (Chart ) in their attempt to generate an ansa -titanocene, while Youngs et al , demonstrated that geometrically constrained bis(trimethylsilyl)dibenzo[ a , f ]fulvalenes, such as 11 , can be readily prepared via oxidative coupling using group 13 metal halides.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray diffraction study revealed that the two N -piperidineethyl-functionalized indenyl ring is coupled through a CC bond with a distance of 1.371(4) Å, which is longer than the standard 1.34 Å expected for the CC bond in ethylene and other planar fulvalenes . The C(3)−C(3a) distance of 1.371(4) Å is also slightly longer than that of 1.359(10) Å found in the π-conjugated fulvalene C 24 H 12 (SiMe 3 ) 2 . It is readily apparent from the crystallographic analysis that the C−C bond lengths in the conjugated fulvalene moiety of 9 alternate between long and short, and there is a significant double-bond localization between (C1)−C(2), C(3)−C(3A), and C(2A)−C(1A) (Table ).…”
Section: Resultsmentioning
confidence: 77%